Age-related macular degeneration: the importance of family history as a risk factor. Issue 3 (23rd August 2011) - Shahid, Humma; Khan, Jane C; Cipriani, Valentina; Sepp, Tiina; Matharu, Baljinder K; Bunce, Catey; Harding, Simon P; Clayton, David G; Moore, Anthony T; Yates, John R W; ,
Abstract : Background: Family history is considered a risk factor for age-related macular degeneration (AMD). With the advent of effective therapy for the disease, the importance of family history merits further investigation. This study quantifies the risk associated with family history, first, by a case–control study of reported family history and, second, by examining the siblings of AMD cases. Methods: The authors recruited cases with advanced AMD, spouses and siblings. All subjects were carefully phenotyped. Clinical findings in the siblings were compared with spouses. Information about family history was collected. The ORs for reported family history of AMD were calculated. Analyses were adjusted for age, smoking and genotype. Results: 495 AMD cases, 259 spouses and 171 siblings were recruited. The OR for AMD was 27.8 (CI 3.8 to 203.0; p=0.001) with a reported family history of an affected parent and 12.0 (CI 3.7 to 38.6; p<0.0001) with a history of an affected sibling. ORs adjusted for age and smoking were higher. Examination of siblings confirmed their increased risk with 23% affected by AMD and an OR of 10.8 (4.5 to 25.8; p<0.0001). Adjusting for age increased the OR to 16.1 (6.2 to 41.8). Conclusion: The risk of AMD is greatly increased by having an affected first-degree relative. Those at risk need to be made aware of this and AMD patients should advise siblings and children to seek prompt ophthalmological advice if they develop visual symptoms of distortion or reduced vision.